Retrieval of Martian Atmospheric CO Vertical Profiles From NOMAD Observations During the First Year of TGO Operations. Issue 3 (7th March 2023) - Modak, Ashimananda; López‐Valverde, Miguel Angel; Brines, Adrian; Stolzenbach, Aurélien; Funke, Bernd; González‐Galindo, Francisco; Hill, Brittany; Aoki, Shohei; Thomas, Ian; Liuzzi, Giuliano; Villanueva, Gerónimo; Erwin, Justin; et al.
Abstract: We present CO density profiles up to about 100 km in the Martian atmosphere obtained for the first time from retrievals of solar occultation measurements by the Nadir and Occultation for Mars Discovery (NOMAD) onboard ExoMars Trace Gas Orbiter (TGO). CO is an important trace gas on Mars, as it is controlled by CO2 photolysis, chemical reaction with the OH radicals, and the global dynamics. However, the measurements of CO vertical profiles have been elusive until the arrival of TGO. We show how the NOMAD CO variations describe very well the Mars general circulation. We observe a depletion of CO in the upper troposphere and mesosphere during the peak period, L S  = 190°–200°, more pronounced over the northern latitudes, confirming a similar result recently reported by Atmospheric Chemistry Suite onboard TGO. However, in the lower troposphere around 20 km, and at least at high latitudes of the S. hemisphere, NOMAD CO mixing ratios increase over 1, 500 ppmv during the GDS (Global Dust Storm) onset. This might be related to the downwelling branch of the Hadley circulation. A subsequent increase in tropospheric CO is observed during the decay phase of the GDS around L S  = 210°–250° when the dust loading is still high. This could be associated with a reduction in the amount of OH radicals in the lower atmosphere due to lack of solar insolation. Once the GDS is over, CO steadily decreases globally during the southern summer season. A couple of distinct CO patterns associated with the Summer solstice and equinox circulation are reported and discussed. Plain Language Summary: CO is an extremely interesting trace species in the Martian atmosphere. It has been used for both dynamical and photochemical studies of the atmosphere. But its vertical distribution has not been systematically measured until the arrival of the Exomars Trace Gas Orbiter (TGO). We use observations of the NOMAD (Nadir and Occultation for Mars Discovery) spectrometer onboard TGO to retrieve full profiles of mixing ratios of CO up to 100 km with a good vertical resolution. The retrievals cover two Martian seasons during which a global dust storm event occurred. We have found the behavior of CO during this event to be governed by local chemistry as well as by the long range transport. During the dust storm, CO mixing ratios are depleted all over the globe while over the southern high latitudes, we discover an increase in CO due to transport from low latitudes during the end of the southern winter. The dynamical effect of global transport is found in the vertical distribution of CO during the southern summer. Another important result, where the local chemistry might be at play is the increase of CO in the low altitudes over low and midlatitudes during the decay phase of the GDS. Key Points: Global map of CO profiles from Nadir and Occultation for Mars Discovery solar occultation observations during the first year of Trace Gas Orbiter operations is presented for the first time During the onset of the 2018 global dust storm (GDS), the CO volume mixing ratios (VMRs) are found to be depleted by 28% at 50 km compared to the average CO VMR values High CO abundance at tropospheric altitudes is observed over NH during decay of the GDS when the atmospheric dust loading is high